Power analysis for asynchronous network‐on‐chip. (18th October 2013) - Abd El Ghany, Mohamed A.; Reehal, Gursharan; Ismail, Mohammed
Abstract: An asynchronous architecture is proposed to achieve a low‐power network‐on‐chip (NoC). The area of the asynchronous switch is increased by 25% as compared to the synchronous switch. However, the power dissipation of the asynchronous architecture could be decreased by up to 55%. Even though clock gating is used, the asynchronous design achieves significant power reduction of 28%. The total metal resource required to implement the asynchronous design is decreased by up to 12%. As technology advances and network density increases, the reduction in power dissipation reaches 22% for 256 IPs with the same chip size. The asynchronous butterfly fat tree (BFT) architecture dissipates the minimum power as compared to other NoC topologies. © 2013 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.